Fiber-optic sensors for cell culture monitoring. - Loo, Quan Chun. (2011)
An optical fibre-based surface plasmon resonance glucose sensor design is proposed based on the optical properties of colloidal gold nanoparticles. In the proposed design, the colloidal surface is functionalised with glucose oxidase to provide selectivity for the sensor. A flow perfusion cell culture system was also developed, consisting of a customised bioreactor, peristaltic pump, and media reservoir. Cell culture experiments were done to compare cell viability in static and perfusion cultures as well as cell behaviour in 2D cultures compared to that of 3D cultures. Cell viability was shown to be higher in perfusion cultures and 3D cultures exhibited cell colonies. Integration of the SPR sensor and the flow perfusion system could potentially create a simple and low cost real-time optical fibre-based bio-sensing system.